CONCEPT OF TASYBIH IN AS-SHAFF VERSE 4: Family Qur’anic Tarbiyah in Gaza Strip - Putri Wulandari; Anggraini, Yola (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This paper aims to analyze the concept of tasybih in QS. As-Shaff verse 4 and the concept of Qur'anic tarbiyah which shapes the spirit of family jihad in the Gaza Strip. Allah Ta'ala provides many tasybih concepts or parables in the holy verses of the Koran to lead humanity to a comprehensive understanding of His word both textually and contextually. One of the verses that contains the concept of tasybih is QS. As-Shaff verse 4. Based on the editorial of this verse, Allah Ta'ala loves the warriors fi Sabilillah who are likened to a solidly constructed building. Today, the Gaza Strip is concrete evidence of Fi Sabilillah's struggle to protect the honor of Muslims and the land of the Anbiya. The method in this writing uses a qualitative descriptive method with a library research approach and literature study. Collecting data by identifying references and reconstructing them from various references such as books, tafsir, journals and previous research. The findings of this article reveal, among other things: first, there is the concept of tasybih in the QS. As-Shaff verse 4; secondly, Qur'anic tarbiyah is an indicator of forming the spirit of jihad in families in the Gaza Strip.